Nonlinear optical response of the KDP single crystals with incorporated TiO₂ nanoparticles in visible range: effect of the nanoparticles concentration - Popov, A.S.; Uklein, A.V.; Multian, V.V.; Pritula, I.M.; Budnyk, P.I.; Khasanov, O.Kh.; Gayvoronsky, V.Ya. (Functional Materials, 2017)
Nonlinear optical response of KDP single crystals with incorporated TiO₂ nanoparticles (NPs) was studied within the self-action of picosecond laser pulses at 532 nm and second harmonic generation at 800 nm femtosecond laser pulses pump. The optical characterization of the composites KDP:TiO2 was provided by elastic scattering indicatrices analyzes at 1064 nm. It was shown the significant reduction of the elastic scattering and self-action effects efficiencies in TiO₂ NPs doped KDP single crystals cut from pyramidal growth sector. The effect was attributed to the reduction of the non-controlled impurities concentration in the KDP:TiO₂ due to the NPs incorporation. The enhancement of second harmonic generation efficiency at about 60 % for pyramidal and 35 % for prismatic growth sectors was observed in composite crystals versus the nominally pure KDP matrix within the femtosecond pulses excitation at 800 nm. The obtained results indicate high potential for utilization of the KDP:TiO₂ single crystals in light frequency conversion."